Confirmation of an association between rs6822844 at the IL2-IL21 region and multiple autoimmune diseases: Evidence of a general susceptibility locus - Maiti, Amit K. (2010)
Objective. Autoimmune diseases often have susceptibility genes in common, indicating similar molecular mechanisms. Increasing evidence suggests that rs6822844 at the IL2-IL21 region is strongly associated with multiple autoimmune diseases in individuals of European descent. This study was undertaken to attempt to replicate the association between rs6822844 and 6 different immune-mediated diseases in non-European populations, and to perform disease-specific and overall meta-analyses using data from previously published studies. Methods. We evaluated case-control associations between rs6822844 and celiac disease (CD) in subjects from Argentina; rheumatoid arthritis (RA), type 1 diabetes mellitus (DM), primary Sjögren's syndrome (SS), and systemic lupus erythematosus (SLE) in subjects from Colombia; and Behçet's disease (BD) in subjects from Turkey. Allele and gene distributions were compared between cases and controls. Meta-analyses were performed using data from the present study and previous studies. Results. We detected significant associations of rs6822844 with SLE (P = 0.008), type 1 DM(P = 0.014), RA (P = 0.019), and primary SS (P = 0.033) but not with BD (P = 0.34) or CD (P = 0.98). We identified little evidence of population differentiation (FST = 0.01) within cases and controls from Argentina and Colombia, suggesting that association was not influenced by population substructure. Disease-specific meta-analysis indicated significant association for RA (Pmeta = 3.61 × 10-6), inflammatory bowel disease (IBD; Crohn's disease and ulcerative colitis) (Pmeta = 3.48 × 10-12), type 1 DM (Pmeta = 5.33 × 10-5), and CD (Pmeta = 5.30 × 10-3). Overall meta-analysis across all autoimmune diseases reinforced association with rs6822844 (23 data sets; Pmeta = 2.61 × 10-25, odds ratio 0.73 [95% confidence interval 0.69-0.78]). Conclusion. Our results indicate that there is an association between rs6822844 and multiple autoimmune diseases in non-European populations. Metaanalysis results strongly reinforce this robust association across multiple autoimmune diseases in both European-derived and non-European populations.